2023
DOI: 10.1002/app.53701
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in hydrogel coatings for urinary catheters

Abstract: Catheters are commonly used in hospital treatment, but most of the medical materials used in the production of catheters are hydrophobic, with high surface friction and weak antibacterial properties, so a large amount of money is spent on the treatment of catheter-related urinary tract infections worldwide every year. To improve the comfort of patients, weaken the friction and damage between urinary catheters and urethra, and reduce economic burden, coating the urethral catheter surface is a good strategy. Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…As a result, the composite coating demonstrated excellent anti-thrombogenic properties, making it a promising material for applications in biomedical devices and implants. Crosslinking using non-toxic Zn-ligand coordination chemistry played a vital role in enhancing the water resistance and mechanical properties of the obtained coatings [ 82 ].…”
Section: Medical Devicesmentioning
confidence: 99%
“…As a result, the composite coating demonstrated excellent anti-thrombogenic properties, making it a promising material for applications in biomedical devices and implants. Crosslinking using non-toxic Zn-ligand coordination chemistry played a vital role in enhancing the water resistance and mechanical properties of the obtained coatings [ 82 ].…”
Section: Medical Devicesmentioning
confidence: 99%
“…Hydrogel-coated catheters do offer short-term benefits of greater patient comfort and reduced microbial adherence. However, their long-term use is a concern due to the cytotoxic potential of hydrogels due to the presence of unreacted monomers, and also the physicochemical properties of the hydrogels are not clearly understood ( Siddiq and Darouiche, 2012 ; Dai et al., 2023 ). This can lead to changes in the surface properties of the hydrogel and promote microbial adhesion, increasing the risk of CAUTI.…”
Section: Anti-fouling Approachesmentioning
confidence: 99%
“…The BP coating technique has been adopted to modify the surface of poly­(dimethylsiloxane) (PDMS). Due to its excellent mechanical property, gas permeability, processability, and transparency, PDMS is widely used to fabricate biomedical devices. , However, the hydrophobicity of PDMS can cause biofouling and friction. , Therefore, researchers have sought to modify the surface of PDMS using MPC polymers. , For example, Goda et al reported modified PDMS using MPC through photopolymerization . BP was coated on PDMS using an acetone solution, and MPC was polymerized on the PDMS surface under UV irradiation.…”
Section: Polymer Brushes: Grafting-from Approachmentioning
confidence: 99%
“…36,37 However, the hydrophobicity of PDMS can cause biofouling and friction. 38,39 Therefore, researchers have sought to modify the surface of PDMS using MPC polymers. 25,40 For example, Goda et al reported modified PDMS using MPC through photopolymerization.…”
Section: ■ Introductionmentioning
confidence: 99%